2014
DOI: 10.4067/s0717-95022014000100039
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometrical Characteristics of Subjects in Predicting Technique Achievements of Basic Turn in Alpine Skiing

Abstract: SUMMARY:This research analyzes the techniques involved in basic turn in relation to anthropometric characteristics of subjects. The aim of this study was to determine the difference in the technique of basic turn performance in relation to anthropometric characteristics of subjects. In a sample of 30 students, average age 22 years, male, measuring by 12 anthropometric measures and a situational-motor test was carried out. Alpine skiing technique was assessed through primary windings, the technical element of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 1 publication
(1 reference statement)
0
1
0
Order By: Relevance
“…The anthropometric methods, defined as measurement of the dimensions of the human body, also have a significant impact on successful competitive alpine skiing (Cramer & Rayan, 2012). Hadzic, Bjelica, Georgiev, Vujovic, and Popovic (2014) analyzed the ANNALES KINESIOLOGIAE • 12 • 2021 • 2 differences in the basic turn technique as one of the ski school elements with regard to anthropometric characteristics. It has been demonstrated that there is a statistically significant difference in the technique of the basic turn with regard to the anthropometric characteristics of the subjects.…”
Section: Introductionmentioning
confidence: 99%
“…The anthropometric methods, defined as measurement of the dimensions of the human body, also have a significant impact on successful competitive alpine skiing (Cramer & Rayan, 2012). Hadzic, Bjelica, Georgiev, Vujovic, and Popovic (2014) analyzed the ANNALES KINESIOLOGIAE • 12 • 2021 • 2 differences in the basic turn technique as one of the ski school elements with regard to anthropometric characteristics. It has been demonstrated that there is a statistically significant difference in the technique of the basic turn with regard to the anthropometric characteristics of the subjects.…”
Section: Introductionmentioning
confidence: 99%